Review papersPrevention of recurrent venous ulceration - Szewczyk, Maria T.; Cwajda-Białasik, Justyna; Jawień, Arkadiusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Conservatively treated venous ulceration should be considered a chronic condition, characterized by consecutive periods of exacerbation, healing, and recurrence. Healing of venous ulceration can be considered a therapeutic success, particularly in the case of chronic wounds. The skin, weakened by many years of venous hypertension, becomes more susceptible to destruction, mechanical injuries, and the progression of the disease. Consequently, the application of tertiary prevention becomes the basis for the prevention of venous hypertension, which can potentially lead to the reactivation of inflammation, trophic lesions, and destruction of tissues.